Antifungal Effect On Candida Albicans And Fusarium Spp. Low-Energy Laser Radiation 630-670Nm In Combination With Pack-Cxl In Fungal Keratitis Experiment In Vivo - Тройченко, Людмила Федорівна; Дрожжина, Галина Іванівна (My University, 2024)
Treatment of fungal keratitis is accompanied by severe consequences due to insufficiently effective local treatment and long-term systemic therapy. The search for new methods of treatment that can provide rapid and complete microbicidal and microbostatic activity is urgent. Aim. To evaluate the antimicrobial effect of PACK -CXL using a photosensitizer 0.1% riboflavin in combination with low-energy laser radiation 630-670nm in models of FK caused by Candida albicans (CA) and Fusarium spp (FS). This study was carried out in the SI " The Filatov Institute of Eye Diseases and Tissue Therapy NAMS of Ukraine" The experimental study was performed on 20 eyes of 10 chinchilla rabbits. Yeast culture of CA was used on 10 eyes, and culture of FS - on 10 eyes. In the control groups (5 paired each eyes) was used anti-fungal treatment. The PACK –CXL using a photosensitizer 0.1% riboflavin was additionally performed in the main groups of 5 eyes. The low-energy laser irradiation 630-670 nm using a photosensitizer 0.1% methylene blue (photodynamic therapy PDT in cliniс) was additionally performed after PACK-CXL in the main group The positive antimicrobial effect of PACK-CXL in combination with low-energy laser radiation of 630-670 nm with 0.1% methylene blue (photodynamic therapy) is shown on the models of FK of moderate degree in an in vivo experiment using CA and FS. It’s confirmed by the absence of fungal flora during microbiological examination and the achievement epithelialization of the cornea 5 days earlier (8.5±0.4 SD), CA moderate model; and 2 days earlier (8.25±0.3), model FS moderate model (р˂0.05) than in the control group. The epithelialization was achieved on 30th day of observation (subtotal intensive vascularized opacification remained) in the main and control groups CA and FS models severe keratitis